Draft Annual Plan 1990-91 Vol-III Government of Tripura - Planning Commission (Planning Commission, 1990)
The Integrated Rural Development Programmed(IRDP) has been under implementation since 1982-83 in the State as a part of the All India Programmed. This Programmed is a Centrally Sponsored Scheme funded by the Centre and the State on 50:50 basis with the aim to assist selected families of target group in rural areas to cross the poverty line by taking self employment ventures by way of mobilising local resources as well as linking Bank credit to the required level of investment with Govt. subsidy.
Government of Tripura